ANALISIS FAKTOR YANG MEMPENGARUHI OPINI AUDIT TERKAIT GOING CONCERN - Saputra, Rudi Eka; Praptoyo, Sugeng (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2017)
This research is meant to find out the influence of audit quality, the previous year audit opinion, companygrowth, corporate financial condition, firm size, and audit evidence to the audit opinion related to going concern.The sample selection has been done by using purposive sampling method on go public companies which are listedin Indonesia Stock Exchange (IDX) with the selected criteria i.e. go public companies which have financialstatement data in 2011-2014 periods, these companies have experienced loss after tax at least 2 periods and usedrupiah currency as the reportingcurrency. Based on the sample research method, 188 go public companieshavebeen obtained as samples. The data analysis of this research has been carried out by using logistic regressionsand the statistic test instrument SPSS 23rd version.The result of this research shows that the variable of previousyear audit opinion has positive influence and corporate financial condition has negative influence to the auditopinion which is related to going concern. Meanwhile, the audit quality, company growth, firm size, and auditevidence do not have any significant influence to the audit opinion which is related to going concern.Keywords: audit opinion, corporate financial condition, going concern.